Spirit lost - Thayer, Nancy, 1943- (C. Scribner's Sons, 1988)
A couple moves to a village on the North Carolina coast, but discovers that their quaint house already has a long-standing tenant. Built 200 years ago by a philandering sea captain, the house is residence to the spirit of an abandoned lover with an insatiable lust and a viciously jealous nature.